Menguatkan Konsep Fikih Sosial dalam Dinamika Interaksi Manusia Perspektif K.H Muhammad Ali Yafie - M. Khairul Arwani Tata (Yayasan Lembaga Studi Makwa, 2022)
Through this paper, the author will try to explain the concept of understanding social fiqh so that human interaction will increasingly bring benefits and away from harmful activities, especially those directly related to nature. The basic theory developed in this discussion is the thought generated by K.H Ali Yafie. The importance of social fiqh and its application as offered by K.H Ali Yafie above makes the author believe that this concept can be presented in the social interactions of Muslims. Because after all, Muslims have a responsibility so that the continuity of life in this world can be used as a facility that will lead to the afterlife, then offer religious understanding (Islamic law) as a form of struggle for the Islamic revolution in alleviating poverty and oppression and through this understanding of social fiqh. it's becoming more and more achievable.